Long jump training emphasizing plyometric exercises is more effective than traditional long jump training: A randomized controlled trial - El-Ashker, S.; Hassan, A.; Taiar, R.; Tilp, M. (Journal of Human Sport & Exercise, 2019)
The aim of the study was to evaluate the impact of an 8-weeksplyometric training program on the sprint and jump performance. The intervention study employed a controlled experimental design with two parallel groups of male long jumpers. While the experimental group (n = 18) trained with plyometric exercises, the control group (n=10) performed classical long jump training. Both groups were examined for athletic performance (30m sprint, standing long jump, vertical jump) and biomechanical parameters of a long-jump movement (max vertical height, horizontal and vertical velocity at take-off, flight time, take-off duration) prior and following the intervention. The experimental group demonstrated significantly better developments than the control group in most of the physical and biomechanical parameters respectively and improved their long jump records. Combining an 8-weeksplyometricprogram with athletics training significantly develops long jump and general athletic performance as well as biomechanical parameters. Therefore, plyometric training can be recommended to athletics coaches as an additional training alternative to improve sprint and long jump abilities in athletes.